EFEKTIVITAS PENERAPAN METODE CONTEXTUAL TEACHING AND LEARNING TERHADAP PENINGKATAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN ILMU PENGETAHUAN ALAM (IPA) KHUSUS DALAM MATERI SIFAT-SIFAT CAHAYA - Rusniati, Ni Wayan (Jurnal Imiah Pendidikan dan Pembelajaran, 2018)
The process and student learning outcomes in science learning material properties of light is a problem faced by class IV SD Negeri 3 Mengwi. Student activity and learning outcomes have not been maximized because the teacher delivered science learning materials using the lecture method. This is the background of the researchers to conduct research with the aim of improving the process and learning outcomes of science with material properties of light with learning models Contextual Teaching and Learning. This research is a type of classroom action research conducted in SD Negeri 3 Mengwi. The subjects of this study were fourth grade students, amounting to 27 students consisting of 14 female students and 13 male students. The implementation of this study used 2 cycles. Instruments used to collect data are observation sheets, interviews, documentation and test questions. The results of this study indicate that science learning outcomes with material properties of light using the Contextual Teaching and Learning model in SD Negeri 3 Mengwi have increased in two cycles with quite satisfactory values. There was an increase in learning outcomes from cycle 1 an average value of 68.51 to 75.37 in cycle 2. In addition, there was an increase in the learning process of students in science learning carried out by teachers using the Contextual Teaching and Learning model. Keywords: Learning process, learning outcomes, Contextual Teaching and Learning